AICCRA Zambia Stories of Gender and Social Inclusion - Mapedza, Everisto D. (2024)
These are Youtube videos showcasing stories of gender and social inclusion in Zambia highlight the experiences of smallholder farmers engaged in aquaculture, solar irrigation, soybeans, maize, beekeeping, and various other agricultural value chains.